Words of Authority: Literature and Power in Bone Society - Feby Triadi (Universitas Cahaya Prima, 2024)
Literature in traditional societies functions not only as a medium of cultural expression but also as a mechanism for legitimizing and negotiating power. This study examines the role of literature—both written and oral—in shaping authority structures within Bone society, South Sulawesi. Using a qualitative ethnographic approach, data were collected through in-depth interviews with local leaders, community elders, and practitioners, combined with participant observation of cultural events and textual analysis of local manuscripts and oral narratives. Thematic analysis revealed that literature serves as a tool for maintaining social hierarchy, asserting political authority, and transmitting cultural norms, while also offering spaces for contestation and negotiation. The study highlights the significance of literature as both a cultural artifact and a medium of power, demonstrating how narratives influence governance, social relations, and cultural memory in Bone society